2021
DOI: 10.3390/mi12101153
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High-Temperature Nitridation and Buffer Layer on Semi-Polar (10–13) AlN Grown on Sapphire by HVPE

Abstract: We have investigated the effect of high-temperature nitridation and buffer layer on the semi-polar aluminum nitride (AlN) films grown on sapphire by hydride vapor phase epitaxy (HVPE). It is found the high-temperature nitridation and buffer layer at 1300 °C are favorable for the formation of single (10–13) AlN film. Furthermore, the compressive stress of the (10–13) single-oriented AlN film is smaller than polycrystalline samples which have the low-temperature nitridation layer and buffer layer. On the one han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In addition, it was confirmed that Al–C, Al–N (or Al–N–C), and N–Al–O bonds exist in the OTM. , During the carbonization of PAN on the AlSb surface, Al migrates to the defect sites of the carbonizing PAN to form Al–C and Al–N bonds . Amorphous Al x O y with oxygen vacancies forms sodiophilic Al–N- and O–Al–N-type bonds in the presence of nitrogen. Such chemical bonds improve the integration between AlSb (with an oxide layer) and N-doped carbon and support the structural stability of the OTM even after battery cycling. Therefore, the OTM is not simply a physically stacked configuration of Sb/AlSb/oxide/N-doped carbon but a form of a chemically integrated structure that formed via multiple intimate junctions.…”
Section: Resultsmentioning
confidence: 92%
“…In addition, it was confirmed that Al–C, Al–N (or Al–N–C), and N–Al–O bonds exist in the OTM. , During the carbonization of PAN on the AlSb surface, Al migrates to the defect sites of the carbonizing PAN to form Al–C and Al–N bonds . Amorphous Al x O y with oxygen vacancies forms sodiophilic Al–N- and O–Al–N-type bonds in the presence of nitrogen. Such chemical bonds improve the integration between AlSb (with an oxide layer) and N-doped carbon and support the structural stability of the OTM even after battery cycling. Therefore, the OTM is not simply a physically stacked configuration of Sb/AlSb/oxide/N-doped carbon but a form of a chemically integrated structure that formed via multiple intimate junctions.…”
Section: Resultsmentioning
confidence: 92%
“…21,22 In comparison to prevalent epitaxial methods like MBE and MOCVD for (11− 22) AlN film growth, HVPE offers advantages such as rapid growth, cost-effectiveness, and high growth temperature, making it ideal for producing large-size high-quality AlN thick films. 23 However, there are limited reports on HVPE epitaxial growth of (11−22) AlN due to the challenges in controlling the process posed by the rapid growth rate. Here, we develop a homemade HVPE system that utilizes induction heating to reach a high temperature of 1480 °C.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As bulk substrates are scarce, semipolar (11–22) AlN films are commonly heteroepitaxially grown on m-plane sapphire substrates using MOCVD, molecular beam epitaxy (MBE), and HVPE. Unfortunately, high-quality semipolar AlN is more difficult to produce than polar AlN because of the anisotropic migration of adsorbed atoms on the growth surface and the mismatch introduced by heteroepitaxy. , In comparison to prevalent epitaxial methods like MBE and MOCVD for (11–22) AlN film growth, HVPE offers advantages such as rapid growth, cost-effectiveness, and high growth temperature, making it ideal for producing large-size high-quality AlN thick films . However, there are limited reports on HVPE epitaxial growth of (11–22) AlN due to the challenges in controlling the process posed by the rapid growth rate.…”
Section: Introductionmentioning
confidence: 99%
“…Two papers [ 15 , 16 ] cover advanced processing techniques. The remaining papers [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ] explore the properties and growth techniques of emerging WBG materials.…”
mentioning
confidence: 99%
“…Regarding the properties and growth of emerging WBG materials, a methodology to synthesize gallium nitride nanoparticles by combining crystal growth with thermal vacuum evaporation is proposed by Fathy et al in [ 22 ]. AlN is explored as an ultra WBG material in three papers: annealing Ni/AlN/SiC Schottky barrier diodes in an atmosphere of nitrogen and oxygen is shown to lead to a significant improvement in the electrical properties of the structures by Kim et al in [ 19 ]; the effect of high-temperature nitridation and a buffer layer on semi-polar AlN films grown on sapphire by hydride vapor phase epitaxy is studied by Zhang et al [ 21 ]; and the thermal annealing of AlN films with different polarities and its impact on crystal quality are studied by in Yue et al in [ 23 ]. The effect of the annealing temperature on the microstructure and performance of sol-gel-prepared NiO films for electrochromic applications is analyzed by Shi et al in [ 17 ].…”
mentioning
confidence: 99%